Socio-Economic And Cultural In Shaping Early Marriage And Stunting In Mempawah Regency - Chainar, Chainar; Desca Thea Purnama; Marini, Marini; Sari, Desita; Wati, Riska (International Journal of Education, Vocational and Social Science, 2023)
Early marriage and stunting in Mempawah Regency are high. The factors causing early marriage and stunting are not only 1 factor, but many factors are interrelated, if you want to overcome stunting thoroughly and effectively, you must find the causative factors associated with early marriage and stunting. This study aims to explain and analyse the relationship between early marriage and stunting from social, economic and cultural perspectives. This research uses descriptive qualitative research methods, informants consist of the Head of KUA, Religious Court, Head of Puskesmas, Midwives and Sub-districts of Mempawah Hilir. Data collection techniques, interviews, observation and documentation and data analysis methods perform data reduction, presentation and conclusions. The results showed a relationship between socio-culture and economics with the formation of early marriage and stunting, all of which are interrelated.